Auditory neuroscience: sound segregation in the brainstem? - Schnupp, J (2008)
Separating a mixture of sounds into its constituent parts is a complex process likely to involve many processing stages. A new study suggests that the first steps in that process may occur already at the level of the first auditory processing centre in the brainstem.